Preparation and Analytical Properties of Amphoteric Chelating Resin - Bhavna A. Shah; Ajay V. Shah; Pathik M. Shah (E-Journal of Chemistry)
The chelating ion exchange resin AFM was synthesized by condensation of anthranilic acid with formaldehyde and m-cresol in DMF media at 100 oC ± 6°C. The identification of resin structure was performed by elemental and FTIR analysis. The thermodynamic parameters such as activation energy (Ea), entropy (S*), enthalpy (H*) and free energy (G*) for thermal decomposition were calculated from thermal data. The morphology of AFM resin shows transition material between crystalline and amorphous phase. The rate of exchange was rapid. i.e. t1/2 < 22 min for Pb(II) and pH dependence of exchange of metal ions on the resin has been determined for several metal ions [Ni(II), Cu(II), Zn(II), Cd(II) and Pb(II)]. Successive separations and recovery of some pair of metal ions [Pb(II)-Cd(II), Pb(II)-Zn(II) and Zn(II)- Cu(II)] have been performed by using distribution coefficient (Kd).